The Challenges of Developing the Alternative to Criminal Prosecution by Taking the England Laws into Consideration - Sheidaeian, Mehdi; Fathi, Mohammad Javad; Mansourabadi, Abas; Nosrati, Yazdan (Journal of History Culture and Art Research, 2017)
The alternatives to the public criminal prosecution have changed the criminal laws. Contrary to the traditional way of settling the disputes which puts emphasis on analyzing the committed crimes, the most significant factor in alternatives to the public prosecution is the conditions, in which the crime happens. The present research seeks to evaluate the problems and challenges in the way of developing and increasing the alternatives to the criminal prosecution by taking the England’s laws into consideration. The alternatives to the criminal prosecution are an intermediate approach that are substituted for criminal prosecution and filing the criminal record away unconditionally. In this way, the aim of the punishments is achieved without imposing the punishment. The alternatives to the criminal prosecutions are based on the ideological, criminological and practical principles. There are many similar cases of imposing alternatives to the criminal prosecutions on the defendants in Islamic teachings. But the alternatives to the criminal prosecutions have not properly developed in Iran. Their development faces with many theoretical and practical challenges. According the investigations, we can define the theoretical challenges faced with alternatives to the criminal prosecutions as the series of the factors and reasons that impede the development of this idea and runs it into the problem. In other words, lack of intention and will to apply these alternatives.